European and national in Antun Gustav Matoš’s travel notes (Colloquia Comparativa Litterarum, 2025)
The dichotomy European/national and its creative power has marked profoundly A. Matoš’s worldly and artistic credo. Two distinguished features pervade his works and his travel notes: the French and the Croatian, the modern and the home-grown. The latter two tend to unite the Western taste with the Croatian propensity for sedition. Antun Matoš’s long-term aspirations strive for a well-maintained balance of the two. His travel notes feature imagologic constructs – a realm of tableaux of every manifestation of the nation’s life and mentality, of European culture and civilization, of domestic developments and human manners. It is precisely by means of his travel notes that Antun Matoš recreated the mythological perception of his life as a patriotically disposed bohemian and an exile, whose works were created solely for the sake of art and literature; a person who disregarded largely the rest of the world. It is lofty artistic ideals that make all disharmonies in life disappear. The dynamic relationship between European and national served as a catalyst for the mixed feelings, typical of his works. Their emblematic presence made them ascend as a categorical imperative, which determined the vitality of his creative capacity, and turned them into a basic guideline for his writings.
Keywords: travel notes; European/national; imagology; modernism